A Giant Solitary Solid Hemangioblastoma: A Case Report and Review of The Literature - Bhandari, Rajeev; Sharma, Gopal R; Bista, Prakash; Jha, Rajiv; Shrestha, Rajendra; Poudel, Prakash (Nepal Journal of Neuroscience, 2017)
We present a case of solitary vascular tumor on posterior cranial fossa in a 15-year-old female who had a complaint of headache on/off for six months with associated dizziness, nausea, vomiting and vertigo. Well circumscribed solid vascular mass was localized on posterior fossa by computed tomography along with magnetic resonance imaging scan. Furthermore, the diagnosis was confirmed by surgical findings and histological examinations.Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page: 47-50